NEW APPROACHES OF ETHICS AND DEONTOLOGY APPLIED TO THE PROFESSIONAL FORMATION OF THE PUBLIC ACCOUNTANT - Polar Falcón, Ernesto Augusto (2010)
The article present progress shows progress process related to the title “New approaches of ethics and deontology applied to the professional formation of the public accountant ”. It begins by informing the assessment process of Proposed Research Study WITH CON - 2010 and the rating with the highest score, in recognition of the importance of the issue to get a better practitioner training in Peru and applied methodology proposed. Offers two interesting posts of the XXVIII Interamerican Jobs CIC - 2009 and an article in the journal Public Accounting, but led to different approaches to the subject of Ethics and Professional Ethics and serve to meet the first objective of the study proposed research, which can increase their sources of information based on the development of two additional targets, now finished and will be presented in due course. The important thing is to create awareness about the need to improve the ethical quality of a public accountant, preparing students for the future development of its activities with a personality framed by ethical principles that are upheld by the Professional Ethics for recognition in Peruvian society, which they render professional services. The entire contents of the two American works and the professional journal, should be released by the Research Institute of the School of Accounting Sciences of San Marcos, to encourage their application in everyday teaching.